PROCESS APPROACH AND COLLABORATIVE LEARNING ANALYSIS ON STUDENTS’ ACADEMIC WRITING - Christianus I Wayan Eka Budiartha; Alexandra Vanessa (ELTR Journal, 2021)
Writing as a productive skill in English has been valued greatly, especially in an academic context. The process approach was started to be considered when teaching writing as it offers more meaningful learning. Furthermore, the approach makes room for collaborative learning between students and teachers. For EFL students whose first language is not English, mastering writing skills could be more challenging. To address the issues, the idea of a writing center has been adapted to a higher educational level for students who want to improve their writing. The study was conducted by using a qualitative descriptive approach and its data collection was carried out through a number of instruments to fulfill the triangulation method of a qualitative approach such as observation, semi-structured interviews, surveys, and corpus-based research. From the eight purposive sampling of tutees and the four tutors, the study concluded that EFL students are not familiar with the process of writing, so many of them consider having support merely on revising their essay draft. Even though collaborative writing was successfully carried out, but EFL students need to improve their independent study to follow up on the discussion they had with the tutors.